Applications of the Bell Numbers on Univalent Functions Associated with Subordination - Sh. Najafzadeh; Mugur Acu (Journal of Function Spaces)
The motivation of the present paper is to define a new subclass of univalent functions associated with the q-analogue of the exponential function and the well-known Bell numbers based on subordination structure. Furthermore, we estimate the coefficient bound and extreme points. Also, geometric properties such as convexity and convolution preserving concept are investigated.